Sejarah Masuknya Islam Di Nusantara Melalui Wali Songgo Relasinya Dengan Masuknya Islam Di Maluku - Hajar Latuapo; Nirmala Nirmala (CV. SINAR HOWUHOWU, 2026)
Islam did not leave a deep and widespread imprint on the local population of the archipelago, as the syncretism of Islam with pre-Islamic values subsequently gave rise to the